Social consent in Ukraine as factor of political stability: challenges and prospects - Авксентьєва, Т. Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Stability examines as a dymanic condition of political system, effective reaction on challenges, adapt to inside and outside changes. The one of the most important factor of stabilization is maintenance of national consent about key positions and values of development in Ukraine. Models of stability are analyzed. It is underlined  in Ukraine stability provides dialectics of objective social and economic indicators, selection of constructive priority of government politics, common efforts of government and society in formation of informational space that corresponded to values of common national sociocultural field.